Adsorptive purification of volatile methyl siloxanes in a digester biogas stream. Issue 11 (10th August 2021) - Aydın Kızılkaya, Yağmur Meltem; Uyak, Vedat
Abstract: BACKGROUND: Siloxanes, one of the various impurity contaminants contained in biogas, comprise a group of volatile organic silicon compounds that pose a major obstacle to biogas application as a consequence of their potential to severely damage energy conversion equipment. Therefore, volatile methyl siloxanes (VMSs) need to be effectively removed from biogas before application. RESULTS: The concentration profile of octamethlytrisiloxane (L3), octamethylcyclotetrasiloxane (D4) and decamethylcyclopentasiloxane (D5) in a biogas were determined. Then in order to investigate the adsorption characteristics of these three siloxane compounds, two commercial granular activated carbons (ACs) were tested for the removal of L3, D4 and D5 in a dynamic adsorption column using biogas streams. The observed concentrations of L3, D4 and D5 in the wastewater treatment plant biogas were 0.62 ± 0.20, 3.07 ± 0.66 and 4.67 ± 1.02 mg m −3, respectively. The best adsorption capacities of L3, D4 and D5 were calculated as 4, 22 and 107 mg g −1, respectively, in real biogas. CONCLUSION: The adsorption capacity of AC2 was found to be higher than AC1 adsorbents for each siloxane compounds studied. Although the elemental and physical structure of the ACs were similar, and AC1's surface area was higher than AC2, AC2 was more effective in siloxane removal due to high mesoporosity causing excess Van der Waals interaction. The relatively higher mesoporous volume and lower rate of mesh size of AC2 resulted in higher adsorption of siloxane compounds. The order of the breaking points was determined as L3 < D4 < D5 in both AC types. © 2021 Society of Chemical Industry (SCI).